Design and synthesis of a dual imageable theranostic platinum prodrug for efficient cancer therapy. Issue 23 (25th February 2019) - Mukherjee, Saikat; Patra, Diptendu; Dash, Tapan K.; Chakraborty, Ipsita; Bhattacharyya, Rangeet; Senapati, Shantibhusan; Shunmugam, Raja
Abstract : Platinum-based chemotherapeutic agents are considered first-line treatments for various cancers but their application is limited by the lack of site specificity and severe side effects. Abstract : Platinum-based chemotherapeutic agents are considered first-line treatments for various cancers but their application is limited by the lack of site specificity and severe side effects. Thus, a multifunctional prodrug should be synthesized with site-specific delivery and in situ monitoring capabilities. Herein, we have designed and synthesized a norbornene based theranostic platinum prodrug for cancer therapy by utilizing the ring opening metathesis polymerization technique. The cobalt carbonyl in the polymeric chain and pyrene end-functionalization in the norbornene backbone provide MRI capability and fluorescence imaging ability of the prodrug, respectively. The ester-linked Pt(ii ) drug showed sustained release, and functionalization of the polyethylene glycol folate moiety ensured water solubility and site-specific therapy. The prodrug formed nanoaggregates in aqueous medium by stabilizing the hydrophobic segment in its core, as is supported by DLS, SEM and EDAX. In vitro studies in HeLa and B16F10 cells showed that the nano-aggregates exhibited increased internalization and an improved anti-proliferative effect compared with free cisplatin. Furthermore, cellular fluorescence images showed uniform cytoplasmic distribution of nano-aggregates. Preclinical pharmacokinetic studies on mice demonstrated longer retention of nano-aggregates. In vivo studies demonstrated increased accumulation in B16F10 melanoma and increased efficiency of the produrg. This new class of dual-imaging, site-specific platinum prodrug system is expected to lead to new opportunities in the field of theranostics.